Effect of Self Regulatory Strategies on Enhancing Teaching Competence among B.Ed Students - Begum, A. J. (INDIAN EDUCATIONAL REVIEW, 2011)
To identify the important components and principles of Self Regulation (SR). (ii) To identify the important Self Regulatory Strategies (SRS) which can enhance the teaching competencies (TC). (iii) To identify the specific teaching competencies which are very essential for successful effective teaching. (iv) To find out the relationship between SRS and specific teaching competencies. (v) To evolve a model to enhance to the TC of B.Ed trainees. (vi) To assess the level of SR and application SRS of B.Ed teacher trainees. (vii) To implement the model evolve in order to enhance the TC of B.Ed teacher trainees through the application of SRS. (viii) To assess the application of SRS among the B.Ed teacher trainees after intervention. (ix) To assess TC after intervention. (x) To find out the relationship between application of SRS and TC. (xi) To identify the specific SRS, which enhance specific TC.